Vitamin D receptor gene BsmI, FokI, ApaI, TaqI polymorphisms and bone mineral density in a group of Turkish type 1 diabetic patients - YAVUZ, DİLEK; YÜKSEL, MERAL (SPRINGER-VERLAG ITALIA SRL, 2011)
Previous studies have suggested an influence of vitamin D receptor alleles on bone metabolism and on susceptibility to type 1 diabetes mellitus in different ethnic populations. We aimed to investigate the distribution of vitamin D receptor (VDR) alleles in relation to biochemical bone turnover parameters and bone densitometry measurements in a group of Turkish type 1 diabetic patients. One hundred and seventeen patients (M/F 57/60, 27.6 +/- A 7.3 y duration of diabetes 8.1 +/- A 6.3 y) and 134 healthy controls (M/F 61/73, 26.2 +/- A 5.3 y) were included in the study. Bone mineral density (BMD) was evaluated by dual-energy X-ray absorptiometry (DEXA). The vitamin D receptor gene (VDR) polymorphisms FokI, Bsm1, Apa1, and Taq1 were examined using a PCR-based restriction analysis. Serum levels of calcium, phosphor osteocalcin, intact parathyroid hormone, and C telopeptide were measured. Vitamin D receptor Bsm1 Fok1, Apa1, and Taq1 genotype distributions were not different between patient with diabetes and control groups. BMD was 0.77 +/- A 0.2 g/cm(2) vs. 0.97 +/- A 0.2 g/cm(2) (P = 0.0001) for the femur, 1.0 +/- A 0.1 g/cm(2) vs. 1.13 +/- A 0.1 g/cm(2) (P = 0.001) for type 1 diabetic patients and controls. Bone turnover markers were significantly lower in type 1 diabetic group. BMD measurements and bone metabolic markers were not different between the genotypes in either the patient with diabetes or the controls. The VDR gene polymorphisms, Bsm1, Fok 1, Apa1, and Taq1 showed no influence on bone metabolism in our group of type 1 diabetic patients.
Keywords: Type 1 diabetes; Vitamin D; Vitamin D receptor gene polymorphisms; Bone mineral density; ASSOCIATION; POPULATION; SUSCEPTIBILITY; OSTEOPOROSIS; PREVALENCE; OSTEOPENIA; MELLITUS; HEALTH; ONSET